Dinâmica populacional e ecologia comportamental da aranha Aebutina binotata Simon, 1892 (Araneae, Dictynidae) em uma área de mata atlântica no nordeste brasileiro - Vale, Jean do (2023)
Population dynamics, the result of spatial interactions over time, are influenced byexogenous and endogenous factors. Phenology can be understood as the analysis oftemporal events and interactions with environmental factors. For spiders, it is related toseasonal reproduction, age structure and the proportion of males and females within agiven population, with four phenological patterns. Spiders are important biologicalcontrol agents in food chains, and are sensitive to changes in climatic conditions, suchas rain and temperature. The order araneae has solitary and social species, wheresociability in populations can be understood as the tendency of organisms of the samespecies to live in groups, developing mutual actions. In the present study (1) weanalyzed and described the phenology, sex ratio and population fluctuation of the socialspider Aebutina binotata (Dictynidae); (2) We investigate how abiotic factors(temperature and precipitation) influence population fluctuation; (3) We checked theduration of A. binotata nests; and (4) we carried out observations of the social behaviorof the species. The research was carried out in a forest area located in Baturité-CE,where a permanent plot of 60x60m was delimited. In each of the 15 marked colonies,the total number of individuals, total females and adult males, total young individualsand the total number of ootheca were recorded monthly over the 10 months. 1496individuals of A. binotata were recorded, of which 220 were considered adults and 1276were considered juveniles. Abiotic factors, such as temperature and precipitation,influenced population fluctuation, highlighting a positive correlation with precipitation(r = 0.81; p = 0.025) and a negative correlation with temperature (r = -0.613; p = 0.05).1496 individuals were recorded, 220 adults and 1276 juveniles. Abundance was notuniform over the 10 months, with the highest number of individuals in February and areproductive peak in June, indicating a stenochronic phenological pattern. Observationsof sociability revealed a lack of task distinction in the nest, but highlighted the crucialrole of adult females in protecting egg sacs. In summary, the study provides insightsinto the complex population dynamics of social spiders, exploring phenology, influenceof abiotic factors and behavior, contributing to a broader understanding of ecosystems.